Thermodynamic assessment of integrated biogas-based micro-power generation system - Hosseini, S. E. (Elsevier Ltd, 2016)
In this paper, a thermodynamic modelling of an integrated biogas (60%CH4 + 40%CO2) micro-power generation system for electricity generation is reported. This system involves a gas turbine cycle and organic Rankine cycle (ORC) where the wasted heat of gas turbine cycle is recovered by closed ORC. The net output power of the micro-power generation system is fixed at 1.4 MW includes 1 MW power generated by GT and 0.4 MW by ORC. Energy and exergy assessments and related parametric studies are carried out, and parameters that influence on energy and exergy efficiency are evaluated. The performance of the system with respect to variation of design parameters such as combustion air inlet temperature, turbine inlet temperature, compressor pressure ratio, gas turbine isentropic efficiency and compressor isentropic efficiency (from the top cycle) and steam turbine inlet pressure, and condenser pressure (from bottoming cycle) is evaluated. The results reveal that by the increase of gas turbine isentropic efficiency, the outlet temperature of gas turbine decreases which incurs negative impacts on the performance of air preheater and heat exchanger, however the energy and exergy efficiency increases in the whole system. By the increase of air compressor pressure ratio, the energy and exergy of the combined cycle decreases. The exergy efficiency of ORC alters by the variation of gas turbine parameters which can be attributed to the variation of temperature discrepancy between gas turbine exhaust temperature and ORC working fluid. Both first and second law efficiency of the combined cycle increases with the enhancement of inlet pressure of ORC turbine due to the mitigation of exergy destruction in heat exchanger. The rate of power generation in ORC increases by the enhancement of ORC turbine inlet pressure, however overall exergy destruction of the cycle decreases slightly.